The political economy of budget trade-offs. (19th October 2018) - Adolph, Christopher; Breunig, Christian; Koski, Chris
Abstract: Because the American states operate under balanced budget requirements, increases in spending in one area typically entail equal and opposite budget cuts in other programs. The literature analysing the correlates of government spending by policy area has mostly ignored these trade-offs inherent to policymaking, failing to address one of the most politically interesting and important dimensions of fiscal policy. Borrowing from the statistical literature on compositional data, we present more appropriate and efficient methods that explicitly incorporate the budget constraint into models of spending by budget category. We apply these methods to eight categories of spending from the American states over the years 1984–2009 to reveal winners and losers in the scramble for government spending. Our findings show that partisan governments finance their distinct priorities by raiding spending items that the opposition prefers, while different political institutions, economic conditions and state demographics impose different trade-offs across the budget.